The Role of Work Competence and Compensation on Icreasing Organitazional Commitment - Ismawanti, Resty; Nahwan, Darwin; Nurzaman, Fahrizal (Journal of Management, 2024)
The purpose of this study is to investigate the impact of job competence and compensation on organizational commitment. The major goal is to determine how much these two variables help to increase employee loyalty to the organization. This study used a quantitative technique, using multiple regression analysis, to investigate the relationship between the independent factors (job competence and compensation) and the dependent variable (organizational commitment). Data was gathered from 100 people working in diverse organizations. The analysis results demonstrate that salary has a significant influence on Organizational Commitment, with a coefficient value of 0.335 and a significance level of 0.000, indicating that a rise in employee salary enhances their commitment to the organization. In contrast, Job Competency has no significant relationship, with a coefficient value of 0.152 and a significance level of 0.117, demonstrating that increasing employees' job competency does not statistically boost their commitment to the firm. The regression model has a R Square of 0.321, indicating that the factors in the model can explain 32.1% of the variability in Organizational Commitment.